Penerapan Technique for Order Preference by Similarity to Ideal (TOPSIS) dalam Pemberian Bonus Karyawan - Ninik Tri Hartanti; Aurellia Quinn Talitha Rahma Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Giving bonuses to employees is one thing that needs to be considered for improving employee performance in a company. Increased employee performance will be able to have a positive impact on the production productivity of a company. The awarding of employee bonuses will go through several stages, initially only by observing directly without taking into account several important aspects in the assessment which in the end can lead to social inequality or jealousy between employees, thereby reducing the quality of production. In this study, the process of giving employee bonuses was carried out using a computational process based on the Technique for Order Preference by Similarity to Ideal (TOPSIS) algorithm, which is one of the algorithms in the decision-making system. Through the application of this method, each employee can be compared based on the criteria determined by the company so that the employee is considered qualified. The criteria used in this study are Skill, length of work, discipline and absenteeism. The results of calculations using the TOPSIS algorithm produce rankings, namely Alternative-1 is ranked 1, Alternative-4 is ranked 2, Alternative-5 is ranked 3, Alternative-3 is ranked 4, and Alternative-2 is ranked 5.